(Energy alternatives and the possibility of substitution) - صالح, لورنس يحيى; محمد, حيدر ظاهر (Journal of Economics and Administrative Sciences, 2018)
Many of the signs that the global energy system indicate the start of a period of transition from total dependence on fossil energy sources, especially oil, into a new era in which alternative energy sources play an important role in meeting the growing needs of energy demand, so sought many of the developed countries through research the studies carried out to try to bring renewable energy sources and non-renewable (shale oil, oil sands, solar energy, wind energy .... etc) replace traditional fossil energy sources (oil, gas, coal) and despite the recent availability dramatically and spread throughout the the world, but they are going to dry up in the foreseeable future. So many countries, especially the developed sought to find alternative sources of energy to meet its needs in the future and ensure the achievement of the current economic, political and environmental goals. Despite the availability and variety of alternative energy sources and spread all over the world, but it is still used widely faced many obstacles and barriers of the most important restrictions technological, economic, and in spite of technological progress and overcome the many obstacles in the field of renewable energies, however, economic obstacles still exist, and Mrs. Mubarak cost, price and restricting dramatically directs States to choose any of the energy used sources by these restrictions, and that the development of alternative energy sources is of extreme economic effects of the oil-producing countries which economies depend on this resource, but the benefits that may be obtained states that increase the use of many alternatives and perhaps the most important of securing a sustainable energy source that meets their needs and future generations of this as well as to the reduction of carbon emissions, which is one of the most serious problems facing the world at the moment .